Activity and selectivity behavior of 1,2-epoxyethylbenzne hydrogenation in carbon dioxide solvent - Rode, Chandrashekhar V.; Hiyoshi, Norihito; Mine, Eiichi; Shirai, Masayuki (Industrial & Engineering Chemistry Research, 2009)
Catalytic hydrogenation of 1,2-epoxyethylbenzene to 2-phenylethanol over charcoal-supported noble metal in carbon dioxide was studied, and the results were compared with those in heptane and methanol. Charcoal-supported palladium and platinum (Pd/C and Pt/C) catalysts were active metal species for the hydrogenation in solvents. The order of activities over palladium and platinum was heptane < carbon dioxide < methanol; however, the formation of dehydroxylated byproduct was suppressed in carbon dioxide solvent. Negative carbon dioxide pressure effect was observed over the Pd/C and Pt/C catalysts in the carbon dioxide solvent.